THE INFLUENCE OF EXCHANGE RATES AND INTEREST RATES ON STOCK PRICE INDICES IN PROPERTY AND REAL ESTATE COMPENIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) - Haeril, Haeril; Sutrisno, Sutrisno; Syamsuddin, M. Syamsunil (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2022)
The objective of this research is to find out the effect of exchange rate and interest rate of the stock price index of Companies’ Property and Real Estate Listed on the Indonesia Stock Exchange. Secondary data concerning exchange rate and interest rate, and stock price index. The sample of this research was 16 companies Property and Real Estate Listed on the Indonesia Stock Exchange period 2012-2014. Data analysis in this research uses multiple llinearinier regression analysis using SPSS 21 software. Based on data analysis, the partially known exchange rate does not significantly affect the company’s stock price index. The interest rate does not significantly affect the company’s stock price index.